Penumbuhan dan Pengembangan Wirausaha Baru pada Era Digital Bagi Generasi Muda di Kelurahan Agrowisata Kecamatan Rumbai Kota Pekanbaru Provinsi Riau - Machasin Machasin; Taufiqurrahman Taufiqurrahman; Dewita Suryati Ningsih; Ezky Tiyasiningsih; Mida Aprilina Tarigan; Arika Fitriani (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2019)
The role of universities in motivating their undergraduate graduates to become a young entrepreneur is very important in growing the number of new entrepreneurs. With the increase in youth entrepreneurship will reduce the increase in the number of unemployed even increase the number of jobs. Pekanbaru City is an area with abundant natural resource potential. For this reason the phenomenon of unemployment among young people, apart from being caused by limited employment, is also due to the synchronization of graduates' qualifications with the needs of the labor market / business (link and match). However, this also explains the low level of entrepreneurship that can be generated from the world of education. To that end, efforts to develop entrepreneurship, especially at the age of youth through training and community service activities must continue to be encouraged. This effort needs to be done as an effort to create young and strong young entrepreneurs. Based on this, a community service program was designed with the title